Community and Village Empowerment Service Efforts to Grow Innovation Through the Village Innovation Program and Creative Industry Innovation - Supratman Tahir (Tinta Emas Publisher, 2023)
This study aims to determine the efforts and inhibiting factors of the Community and Village Empowerment Services in Growing Community Innovation through Creative Industries in Sinjai Regency. The research technique is descriptive qualitative. Data collection techniques are observation, documentation and interviews. The informants consisted of the Head of Service, Secretary, Head of Development Economics, Natural Resources and TTG of Community and Village and Community Empowerment Services. Data analysis techniques namely data reduction, data presentation and giving conclusions. Various efforts have been made by the PMD Service in cultivating community innovation through the creative industry, namely carried out with various strategies or approaches that are massive, structured and based on procedures that apply according to their main tasks and functions. Regarding the various problems and obstacles faced, such as funds, human resources at the Community and Village Empowerment Service and human resources that are endeavored to be fostered in the village, and also not spared from regulatory issues that often change with political changes.